"SO MUCH FOR ACCESS:" DIFFERENCE, BENEFITS, AND BARRIERS AT HAWAII'S SHORELINES. Issue 4 (8th August 2022) - Gould, Rachelle K.; Morse, Cheryl E.; Brooks, Jill; Adams, Alison
ABSTRACT: Hawai'i Island's shorelines provide intangible and tangible benefits for the island's residents and visitors. This paper examines residents' access to, values associated with, and uses of Hawai'i Island's blue spaces. It finds that Native Hawaiian residents and those who ascribe to Native Hawaiian cultural values encounter barriers to experiencing the diverse shoreline benefits they value. In-depth interviews reveal that although all shorelines on Hawai'i Island are designated as public property, individuals' abilities to access shorelines and shoreline benefits are not equal in this postcolonial context. We find that the Native Hawaiian ethic of care and reciprocity is present among the some of island's long-time residents, and suggest that an extension of this ethic into formal shoreline regulation and community and tourist educational programming may ensure culturally appropriate access to the diverse benefits blue spaces provide.